Treatment with Proprotein Convertase Subtilisin/Kexin Type 9 Inhibitors (PCSK9i): Current Evidence for Expanding the Paradigm? - Rosaria Vincenza Giglio BD, PhD; Emir M. Muzurović MD, PhD; Angelo Maria Patti MD, PhD; Peter P. Toth MD, PhD; Manyoo A. Agarwal MD; Wael Almahmeed MD; Aleksandra Klisic MD, PhD; Marcello Ciaccio MD, PhD; Manfredi Rizzo MD, PhD (SAGE Publishing, 2023)
Background: Proprotein convertase subtilisin/kexin type 9 inhibitors (PCSK9i) are low-density lipoprotein cholesterol (LDL-C)-lowering drugs that play a critical role in lipoprotein clearance and metabolism. PCSK9i are used in patients with familial hypercholesterolemia and for the secondary prevention of acute cardiovascular events in patients with atherosclerotic cardiovascular disease (CVD). Methods: We focused on the literature from 2015, the year of approval of the PCSK9 monoclonal antibodies, to the present on the use of PCSK9i not only in the lipid field but also by evaluating their effects on metabolic factors. Results: PCSK9 inhibits cholesterol efflux from macrophages and contributes to the formation of macrophage foam cells. PCSK9 has the ability to bind to Toll-like receptors, thus mediating the inflammatory response and binding to scavenger receptor B/cluster of differentiation 36. PCSK9i lower the entire spectrum of apolipoprotein B-100 containing lipoproteins (LDL, very LDLs, intermediate-density lipoproteins, and lipoprotein[a]) in high CVD-risk patients. Moreover, PCSK9 inhibitors are neutral on risk for new-onset diabetes mellitus and might have a beneficial impact on the development of nonalcoholic fatty liver disease by improving lipid and inflammatory biomarker profiles, steatosis biomarkers such as the triglyceride-glucose index, and hepatic steatosis index, although there are no comprehensive studies with long-term follow-up studies. Conclusion: The discovery of PCSK9i has opened a new era in therapeutic management in patients with hypercholesterolemia and high cardiovascular risk. Increasingly, there has been mounting scientific and clinical evidence supporting the safety and tolerability of PCSK9i.